2002
DOI: 10.1152/jn.00221.2001
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Medullary Raphe-Spinal Neurons in Cutaneous Vasoconstriction: An In Vivo Electrophysiological Study

Abstract: Nalivaiko, Eugene and William W. Blessing. Potential role of medullary raphe-spinal neurons in cutaneous vasoconstriction: an in vivo electrophysiological study. J Neurophysiol 87: 901-911, 2002; 10.1152/jn.00221.2001. In rabbits, raphe magnus/pallidus neurons form a link in the CNS pathway regulating changes in cutaneous blood flow elicited by nociceptive stimulation and activation of the central nucleus of the amygdala. To characterize relevant raphe-spinal neurons, we performed extracellular recordings fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…6 Thus, serotonergic inputs may influence sympathetic outflow both at medullary and spinal levels. The rostral medullary raphe, including the RPa and RMg, controls sympathetic outflow to the brown fat 5 and skin blood vessels 3,4 and has been implicated in thermoregulatory responses to cold stimuli, as well as skin vasoconstrictor responses to pain or amygdala stimulation. 4 Although…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Thus, serotonergic inputs may influence sympathetic outflow both at medullary and spinal levels. The rostral medullary raphe, including the RPa and RMg, controls sympathetic outflow to the brown fat 5 and skin blood vessels 3,4 and has been implicated in thermoregulatory responses to cold stimuli, as well as skin vasoconstrictor responses to pain or amygdala stimulation. 4 Although…”
Section: Discussionmentioning
confidence: 99%
“…2 Likewise, in patients with cystic fibrosis resulting from premature stop codon mutations in the CFTR gene, treatment with gentamicin resulted in increased CFTR expression and chloride conductance across the nasal epithelium. [3][4][5] Despite these encouraging results, two clinical trials of gentamicin treatment in DMD have observed no changes in muscle strength or increased dystrophin…”
Section: Ann Neurol 2004;55:422-426mentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, we antidromically activated medullary raphé-spinal neurons and examined the subclass of cells activated by electrical stimulation of the trigeminal tract (a procedure that vigorously constricts the ear pinna bed). The discharge of raphé-spinal neurons with axonal conduction velocities as high as 30 m/s was substantially increased by this procedure (34). The pathway from the trigeminal tract to the spinal cord is presumably exclusively via the raphé, since inactivation of this region with muscimol entirely abolishes trigeminally elicited increases in sympathetic cutaneous vasomotor discharge (7,40).…”
Section: Axonal Conduction Velocity Of Raphé-spinal Neurons Activatinmentioning
confidence: 94%
“…The autonomic regulation of skin microcirculation is a highly complex and integrated process, whose ''driving neurons" are located in the brainstem, more specifically in the rostral ventromedial medulla, close to the integrative area called ''formatio reticularis" [22][23][24]. One of the most important functions of skin microcirculation appears to be its role in thermoregulation: by dilatation or constriction they allow for a rather efficient heat dissipation [25].…”
Section: Hypothesismentioning
confidence: 99%